2011
DOI: 10.1111/j.1600-0463.2011.02793.x
|View full text |Cite
|
Sign up to set email alerts
|

VIM and IMP metallo-β-lactamases and other extended-spectrum β-lactamases in Escherichia coli and Klebsiella pneumoniae from environmental samples in a Tunisian hospital

Abstract: An extremely drug-resistant Enterobacteriaceae species emerged in Kasserine Hospital, Tunisia between 2009 and 2010 causing a local outbreak. We aimed to characterize extended-spectrum β-lactamase (ESBL) and metallo-β-lactamase (MBL)-producing Enterobacteriaceae from the hospital environment. Swabs were collected from ten different wards from Kasserine Hospital, Tunisia. A total of 46 isolates were cultured onto MacConkey agar supplemented with ceftazidime to select for ESBL-producing Enterobacteriaceae. Ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…Plasmid-encoded MBLs emerged in Japan in 1990 with the IMP family of enzymes (151) and in Italy in 1997 with the VIM ␤-lactamases (152), causing some to predict a global epidemic of multidrug-resistant MBL-producing Gram-negative bacteria. Although the IMP and VIM MBL families began to expand after 2000 (Table 3), outbreaks associated with these enzymes have tended to be small, limited in time, and localized to specific geographical regions (153)(154)(155)(156)(157).…”
Section: ␤-Lactamases In Gram-negative Bacteriamentioning
confidence: 99%
“…Plasmid-encoded MBLs emerged in Japan in 1990 with the IMP family of enzymes (151) and in Italy in 1997 with the VIM ␤-lactamases (152), causing some to predict a global epidemic of multidrug-resistant MBL-producing Gram-negative bacteria. Although the IMP and VIM MBL families began to expand after 2000 (Table 3), outbreaks associated with these enzymes have tended to be small, limited in time, and localized to specific geographical regions (153)(154)(155)(156)(157).…”
Section: ␤-Lactamases In Gram-negative Bacteriamentioning
confidence: 99%
“…) and the hospital environment (Chouchani et al . ) over the last 5 years, it has not been until very recently when the first carbapenemase‐producing E. coli was detected in pets (Yousfi et al . ) and livestock animals (Braun et al .…”
Section: Esbl Plasmid‐mediated Ampc and Carbapenemase‐producing E Cmentioning
confidence: 99%
“…Considering carbapenemase production among E. coli isolates in the African continent, although many descriptions have been reported in humans (Robin et al 2010;Moquet et al 2011;Barguigua et al 2013;Leski et al 2013;Mushi et al 2014) and the hospital environment (Chouchani et al 2011) over the last 5 years, it has not been until very recently when the first carbapenemaseproducing E. coli was detected in pets (Yousfi et al 2016) and livestock animals (Braun et al 2016). The previously described study, conducted in different dairy cattle farms from Egypt, reported four E. coli strains harbouring bla OXA-48 and one carrying bla OXA-181 carbapenemase genes, all of them phenotypically resistant to meropenem and imipenem.…”
Section: Esbl Plasmid-mediated Ampc and Carbapenemase-producing E Cmentioning
confidence: 99%
“…While VIM-1-derived enzymes have been reported largely for Enterobacteriaceae from around the world, especially from Greece but also recently from Belgium (4), VIM-2 has been associated mostly with Pseudomonas aeruginosa (32). The occurrence of VIM-2 has nevertheless also been reported for clinical isolates of Enterobacteriaceae from Asia (17,24,39), Mexico (28), Argentina (16), and Tunisia (10). Moreover, a recent report showed the presence of VIM-2 in Enterobacter ludwigii isolated from sewage water of a hospital, highlighting the involvement of environmental bacteria as potential reservoirs for the dissemination of clinically relevant metallo-␤-lactamase resistance genes (37).…”
mentioning
confidence: 99%